Reading Art Therapy Practices as a Media for the Distribution of Mental Wellbeing in Indonesia - Waryanti, Dessy Rachma (Indonesian Journal of Visual Culture, Design, and Cinema, 2024)
Art practices have become an effective means of facilitating recovery and maintaining individual mental health in an activity called art therapy. Whether carried out according to medical advice in the form of intervention or non-intervention, both types of art therapy delivery practices have produced many positive things. This research article wants to read how art therapy practices and art itself are used in different social and scientific disciplines where the application is carried out according to scientific methods. Happiness, the regulation of human consciousness and control of emotions, can apparently be triggered by artistic activities and is accepted in medical practices. Based on the research method in this article which uses a literature study approach, there are differences from those in America and England. In Indonesia, the practice of art therapy still stands alone and is carried out by medical personnel, psychologists and psychiatrists. This is different from the practices carried out by Adrian Hill, Edward Adamson and Edith Kramer. The three art therapy experts explained that in the practice of art therapy, a medical therapist must be accompanied by an art practitioner or someone who has an art educational background as a counselor. It is important to ensure that the art therapy process is carried out with a deep understanding of creative exploration, aesthetics and local cultural context. The rest of this article also examines that art therapy is also very beneficial for the general public without diagnosed health problems in maintaining their mental health.